Virtual-reality-based methodology for modelling and verifying shop floor control systems - Manesh, H. F.; Hashemipour, M. (Sage Publications Ltd, 2010)
The design and development of shop floor control systems (SFCSs) in automated manufacturing plants requires careful thought to ensure that the manufacturing system successfully satisfies the demands of today's competative marketplace. This paper presents a methodology for the development of SFCSs that is based on virtual reality (VR) in order to assist the system designer at each stage of development. Exploiting VR helps the user to collect valid information quickly and in a correct form by putting the user and the information support elements in direct relation with the operation of the system in a more realistic environment. A VR-SFCS prototype tool is designed as a software system to realize the features outlined in each phase of the methodology. A set of rules and a knowledge base is appended to the methodology to remove any inconsistency that could arise between the material and the information flows during the development. A novel environment for matching the physical and the informational model domains is recommended in order to delineate the system requirements specification.
Keywords: automated manufacturing systems; shop floor control system; virtual reality; virtual factory